Resection of a Lumbar Intradural Extramedullary Schwannoma: 3-Dimensional Operative Video. Issue 5 (30th May 2019) - Dekker, Simone E; Glenn, Chad A; Ostergard, Thomas A; Smith, Mickey L; Rothstein, Brian D; Ray, Abhishek; Bambakidis, Nicholas C
Abstract: This 3-dimensional operative video illustrates resection of a lumbar schwannoma in a 57-yr-old female who presented with right lower extremity numbness, paresthesias, as well as a long history of lower back pain with rest. On magnetic resonance imaging (MRI), there was evidence of an intradural extramedullary enhancing lesion at L5, nearly completely encompassing the spinal canal. This video demonstrates the natural history, treatment options, surgical procedure, risks, and complications of treatment of these types of tumors. The patient underwent a posterior lumbar laminectomy with a midline dural opening for tumor resection. The tumor was encountered intradurally and electromyography recording confirmed that the tumor arose from a lumbar sensory nerve root. The sensory root was then divided and the tumor was then removed. The mass was removed en bloc and histopathologic analysis was consistent with a schwannoma. Postoperative MRI demonstrated gross total resection of the patient's neoplasm with excellent decompression of the spinal cord. The patient had an uneventful postoperative course with full recovery and complete resolution of her back pain and leg paresthesias.